Utilizing CMC/ZnO Blends Made at Various Mixing Ratios on Paper Surfaces and Their Impact on Paper Characteristics - Orçun Çağlar Kurtuluş (BioResources, 2025)
Surface treatments of paper and paper-based compounds are one of the most effective methods for improving different specifications of paper products, such as printability, paper strength values, absorption performance, and diminished surface roughness. In this study, cellulose derivatives of carboxymethyl cellulose (CMC) and zinc oxide (ZnO), an inorganic antibacterial material, were prepared in varying concentrations (1/1, 1/0.5, and 1/0.25) and applied to standard filter paper by the dip-coating method to examine the combined effects of these chemicals on paper properties and the performance of the investigation papers as a food packaging material. Density, dry-wet strength, Cobb values, oil-dye absorption, and air permeability of papers were investigated in addition to degradation tests, Fourier transform infrared spectroscopy, antibacterial activity, and scanning electron microscopy images. The density values of papers were determined between 0.421 and 0.468 g/cm3. Although determined by different techniques, oil absorption and dye absorption performances showed similar patterns, and the addition of ZnO into the composition caused a decrease in the absorption performances. Dry strength and Cobb values increased with the ZnO addition, and strength values increased. Wet strength values. According to all of the findings, these papers would make excellent food packaging materials, particularly for dry, low-weight products.